2017
DOI: 10.20396/bjos.v16i0.8650500
|View full text |Cite
|
Sign up to set email alerts
|

Influence of enamel acid-etching on mechanical properties and nanoleakage of resin composite after aging

Abstract: Aim: The aim of this study was to evaluate how acid-etching of the cavosurface enamel in Class I resin composite restorations influences the bond strength to the pulpal wall and the restoration, Knoop microhardness and nanoleakage after thermomechanical aging. For this research 76 fresh human molars were selected and restored with Silorane or Clearfil SEBond/Z350XT composite divided in 4 groups (Silorane system restored with or without enamel cavosurface acid-etching and Clearfil SEBond/Z350XT with or without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
3
0
3
Order By: Relevance
“…Bond strength can be evaluated by a variety of testing methods including shear, micro shear, and micro tensile tests. In this study, micro tensile bond strength (μTBS) was chosen as it permits the alignment of different samples in a proper way resulting in a stress pattern with a homogeneous distribution; also, it facilitates the longitudinal sectioning of the samples and provides better economic sample use (23) .…”
Section: Discussionmentioning
confidence: 99%
“…Bond strength can be evaluated by a variety of testing methods including shear, micro shear, and micro tensile tests. In this study, micro tensile bond strength (μTBS) was chosen as it permits the alignment of different samples in a proper way resulting in a stress pattern with a homogeneous distribution; also, it facilitates the longitudinal sectioning of the samples and provides better economic sample use (23) .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the Charisma Diamond resin was used, which showed no difference to the other composite resins. This resin has the TCD-urethane monomer, which according to the manufacturer, discards the use of diluting monomers and presents a molecule with three rings connected in a central portion, increasing the flexibility of the monomer and decreasing polymerization shrinkage 6,25 . This composite resin was expected to have better bonding properties due to such a characteristic, but this was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring of bond strength can be evaluated by a variety of testing methods including shear, microshear and microtensile tests. In this study, microtensile bond strength (μTBS) was chosen as it permits the alignment of different samples in a proper way which result in a stress pattern with a homogeneous distribution also it facilitate the longitudinal sectioning of the samples and it provides better economic sample use and it can test the irregular surfaces [18] . The μTBS of each beam was calculated as the force of failure divided by the bonded cross-sectional surface area and expressed in MPa as Zhao et al in 2006 have done [19] .…”
Section: Discussionmentioning
confidence: 99%